(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
The synthesis of new 1,2,3-triazoles has been actualized by means of the reaction of dipolar1,3-cycloaddition of organic azides to the γ-lactones containing terminal triple bond. The synthesized compounds previously were nondescript in literature. High yields of the final products ensured the optimal reaction conditions.